2021
DOI: 10.1021/acs.jpcc.1c03937
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learned Decision Trees for Predicting Gold Nanorod Sizes from Spectra

Abstract: Electron microscopy is often required to correlate the size and shape of plasmonic nanoparticles with their optical properties. Eliminating the need for electron microscopy is one crucial step toward in situ sensing applications, especially for complicated sample conditions such as during irreversible chemical reactions or when particles are embedded in a matrix. Here, we show that a machine learning decision tree can accurately predict gold nanorod dimensions over a wide range of sizes. The model is trained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 75 publications
0
34
0
Order By: Relevance
“…[8][9][10][11][12][13] Instead of these traditional analytical frameworks, machine learning (ML) algorithms demonstrate immense potential to analyze plasmonic nanoparticles' optical spectra and achieve accurate estimations of their dimensional parameters. [14][15][16][17][18] ML algorithms can (1) uncover functions that connect inputs with outputs and in the process elucidate complex underlying trends/patterns within a dataset and (2) continuously learn in every iteration to improve prediction accuracy. [19][20][21] The key to ML success is the quality of input data (features) that are used in the algorithm.…”
Section: Nanoscale Horizonsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10][11][12][13] Instead of these traditional analytical frameworks, machine learning (ML) algorithms demonstrate immense potential to analyze plasmonic nanoparticles' optical spectra and achieve accurate estimations of their dimensional parameters. [14][15][16][17][18] ML algorithms can (1) uncover functions that connect inputs with outputs and in the process elucidate complex underlying trends/patterns within a dataset and (2) continuously learn in every iteration to improve prediction accuracy. [19][20][21] The key to ML success is the quality of input data (features) that are used in the algorithm.…”
Section: Nanoscale Horizonsmentioning
confidence: 99%
“…[19][20][21] Current ML-UV-vis studies employ statistical feature selection methods to compute the contribution of each datapoint (feature) towards prediction report significant errors of B10%. 16,18 This is because each datapoint in the spectra (assuming 1 datapoint/nm, we will have B600 datapoints/spectra) encodes very little information. It is also challenging to find the optimal number and permutation of datapoints (feature) within the dataset for nanoparticle size prediction.…”
Section: Nanoscale Horizonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, inferring structural information directly from the optical spectra can be investigated as another strategy to overcome the limitations of electron beam damage, temporal resolution and statistics arising from the need of EM to correlate morphology to optical properties of NSs. 78,[135][136][137][138] For example, Payne et al used high throughput quantitative extinction microscopy in combination with electromagnetic simulations to measure the size and shape of metal NSs fully optically. 135 Dawson and co-workers demonstrated that it is also possible to detect the shape of anisotropic gold NSs in dispersion by optical means.…”
Section: Discussionmentioning
confidence: 99%
“…It may become an extremely useful assisting tool for experimental measurements. The demonstrations in this field include characterization of orientation [204] or size [205] of metallic nanoparticles using measured spectral data. ML find its applications in a variety of microscopy and imaging techniques [206,207] as well as for tracking [208], localization [209] and analysis of single molecules [210].…”
Section: Perspective and Outlookmentioning
confidence: 99%